LASIK Videos on TikTok: A Content Analysis of the Top 100 Videos - Firas F. Haddad; Joanna S. Saade (Journal of Ophthalmology)
Introduction. Social media has increasingly become a prominent source of health information. Platforms like TikTok that allow for videos to reach millions of viewers have become among the most common platforms to share and receive health information. Laser in situ keratomileusis (LASIK) videos and patients’ experiences are commonly discussed on social media. The quality of these videos remains to be assessed. The aim of this study is to evaluate the content, quality, and reach of the top 100 videos related to LASIK eye surgery on TikTok. Methods. Video quality was assessed using the DISCERN, JAMA, and GQS instruments which have all been proven to be both reliable and valid. Results. 100 videos were included in the study. Results showed that the videos have an immense reach with a total view count of 245 million views and 21.9 million likes. Two thirds of the videos were posted by personal accounts as compared ophthalmologists that only constituted 26% of the content. Healthcare professionals produced higher quality videos compared to nonhealthcare professionals (p<0.0001) although there was no significant difference in video duration (p=0.18). Increased duration, view count, comments, shares, saves, and views/day were all associated with increased DISCERN score and quality of the videos. Educational videos were of higher quality compared to entertainment videos, and videos outlining the procedure details had the highest quality score. Conclusions. LASIK videos on TikTok have established a wide reach, whereby viewers are highly interacting and viewing these videos. It appeared that viewers interacted more with the higher quality videos. Ophthalmologists approximately only contributed to a quarter of the videos analyzed in this study. This highlights the need for ophthalmologists to establish a presence on TikTok and produce high quality videos.